Penggunaan Metode Pembelajaran Card Sort Untuk Meningkatkan Hasil Belajar PAI Siswa Kelas VII SMPN 1 Kecamatan Kapur IX - Meyriza Hamda; Zulfani Sesmiarni; Rodi Rodi; Desri Wahyuni (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research was motivated by the low ability of children in reading the Al-Quran in class VII SMPN 1 Kapur IX District. One solution to this problem is to implement activities using the Cart Sort method. This research aims to improve the Al-Quran reading ability of children in Class VII SMPN 1 Kapur IX District. The method used in this research is the Classroom Action Research (PTK) method. This classroom action research was carried out in 2 cycles, in each cycle there were 2 meetings. Data collection techniques used were observation and documentation. The results of this study show an increase in children's scores from pre-action, cycle I and cycle II which can clearly be described as follows: the BB value at pre-action was 6 children or 50%, then in cycle 1 it became 5 children or 40%, then in cycle II it became 0 children or 0% MB value in pre-action 2 children or 10%, then in cycle 1 it becomes 2 children or 10% In cycle II it becomes 0 children or 0%, BSH value in the action there are 2 children or 10%, then in cycle 1 becomes 2 children or 10%, for cycle II 2 children 10%, BSB value in pre-action 2 children or 10% then In cycle 1 it becomes 5 children or 40% and at the end of cycle II increases to 11 children or 90%. Based on the results of the research above, the researcher suggested to teachers to use the cart sort method as an alternative activity to improve children's ability to learn PAI. Keywords: , ,